2021
DOI: 10.2174/2210681209666191128155819
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity Studies of Curcumin Loaded-cockle Shell-derived Calcium Carbonate Nanoparticles

Abstract: Background: Cockle shell-derived calcium carbonate nanoparticles (CSCaCO3NP) are natural biogenic inorganic material that is used in drug delivery mainly as a bone-remodeling agent as well as a delivery agent for various therapeutics against bone diseases. Curcumin possess wide safety margin and yet puzzled with the problem of poor bioavailability due to insolubility. Propounding in vitro and in vivo studies on toxicity assessments of newly synthesized nanoparticles are ongoing to overcome some crucial challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…For instance, calcite in eggshells, vaterite in fish otoliths and aragonite in mollusc shells. 4–7 The application of eggshell particles processed by simple mechanochemical methods has been extensively studied so far in different fields such as filler in polymers, 8–10 wastewater purification, 11–13 drug delivery and biomedical application. 14,15 The mechanochemical methods refer to the process of obtaining microparticles by applying mechanical energy at ambient temperature, such as grinding, ball milling, or mortar and pestle techniques.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, calcite in eggshells, vaterite in fish otoliths and aragonite in mollusc shells. 4–7 The application of eggshell particles processed by simple mechanochemical methods has been extensively studied so far in different fields such as filler in polymers, 8–10 wastewater purification, 11–13 drug delivery and biomedical application. 14,15 The mechanochemical methods refer to the process of obtaining microparticles by applying mechanical energy at ambient temperature, such as grinding, ball milling, or mortar and pestle techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The approach suggested by (Hamidu et al, 2019, andMailafiya et al, 2021) was adopted with some changes to load CaCO3NPs (27,28). A mixture was created using 1 mg rhBMP-2, 15 mg CaCO3NPs, and 3 ml deionised water.…”
Section: Preparation Of Rhbmp-2 Loaded Caco3nps (Rhbmp-2-caco3nps)mentioning
confidence: 99%
“…Cockle shells have a high calcium carbonate content [ 9 ]. These shells are abundantly available at a minimal cost, and in vitro studies have demonstrated that the calcium carbonate derived from cockle shells is biocompatible [ 10 ]. Nanoparticles derived from cockle shells have been used in medicine as a drug carrier targeting cancer cells [ 11 ].…”
Section: Introductionmentioning
confidence: 99%